A qualitative study to explain the determinants of naswār consumption from the point of view of its consumers - Mohammad-Rafi Bazrafshan; Amir Mansouri; Behnam Masmouei; Noureddin Niknam; Fatemeh Zahedi (Journal of Education and Health Promotion)
BACKGROUND: One of the health problems related to tobacco that is increasing in society is the consumption of naswār. This study aimed to investigate the determinants of naswār consumption from the point of view of its consumers. MATERIALS AND METHODS: In this qualitative study, 47 men with an age range of 23- 54 years who consumed naswār from the southern cities of Fars province in Iran were selected and interviewed. These participants were selected using purposive and snowball sampling methods, and data was collected using semi-structured interviews. Data analysis was done using the conventional approach of qualitative content analysis. RESULTS: Three main categories were extracted: (1) Individual factors and beliefs related to naswār consumption (Non-addictive, similar and replacement with smoking, Not causing confusion, Being relaxing and enjoyable, increasing the effect of using other substances, reducing fatigue, causing body aches due to lack of use, having long effect, not causing physical problems, not causing weakness, having fast effect, increasing energy to work), (2) Environmental factors (being available, Having the low price, being consumed anywhere, being easy to store and carry, Not understanding others), and (3) Social factors (as a hobby, lack of entertainment, relatives and friends of the consumer, lack of ban on the consumption of naswār, lack of family opposition). CONCLUSION: As the results showed, there are many reasons for consuming naswār based on individual, environmental, and social factors. Formulation of laws, health policies, and education can be effective in adopting strategies to prevent and control the consumption of naswār.